Evaluation of arthroscopic Bankart repair in recurrent shoulder dislocation - Mohapatra, R. G. Asutosh; Kumar, Jitendra (International Journal of Research in Orthopaedics, 2019)
Background: Our aim was to study the surgical and functional outcome and postoperative shoulder motion following, arthroscopic repair of the Bankart lesion of the shoulder with suture anchors. Methods: This was a study of arthroscopic Bankart repair in recurrent anterior shoulder dislocation with suture anchors in 20 patients. Most of patients had symptoms for a period ranging from 1 to 2 years and 1- 4 recurrent dislocation episodes preoperatively. Necessary radiological and haematological investigations were done. The post-operative x-rays were evaluated and the post-operative rehabilitation evaluation done at 3 weeks, 6 weeks, 12 weeks, 6 months and 1 year, for any recurrence of symptoms. Results: In our study of 20 patients, with the mean follow up period of 12 months, the mean Rowe score post-operatively improved to 94 from a pre-operative mean score of 56.25. Out of 20 patients none had episodes of recurrent dislocation. In 15 patients 3 suture anchors were used and in 5 patients 2 suture anchors used intra operatively. The range of movement – external rotation in 90º of abduction improved in 17 patients (85%). Conclusions: We concluded that arthroscopic Bankart repair in recurrent anterior shoulder dislocation with suture anchors is effective in providing better shoulder function with range of movement and lower rate of recurrence.